The Influence of the Rumah Gemilang Indonesia Program by LAZ Al Azhar of Depok City on the Economic Independence of its Beneficiaries - Novia Fitri Azzahra; Ajeng Kartika Galuh (Islamic Economics and finance in Focus, 2026)
Indonesia’s demographic dividend presents both opportunities and challenges, particularly as high unemployment among the working-age population risks hindering the younger generation’s economic independence; thus, sustainable empowerment strategies through the use of productive zakat are needed. This study aims to analyze the influence of educa-tion and training in the Rumah Gemilang Indonesia (RGI) Program of LAZ Al Azhar in Depok City on the economic independence of alumni. The study employs an associative quantitative approach with a sample of 96 alumni selected via simple random sampling. Data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that education and training have a positive and significant effect on economic independence. This suggests that edu-cation and training based on productive zakat contribute to promoting economic inde-pendence. These findings indicate that the utilization of productive zakat through educa-tion and training can serve as an effective empowerment strategy to enhance the economic independence of zakat recipients and strengthen the empowerment programs of zakat in-stitutions.